PROSPECTS FOR EXPANDING INTERNATIONAL ACTIVITIES OF UKRAINIAN COMPANIES IN THE COFFEE AND COFFEE EQUIPMENT MARKET - KHACHATRYAN, Valentyna; STRATIICHUK, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The results of the operation of international companies have a significant impact on the economy of each country, allow to build close foreign economic ties with international partners. In today's economic conditions, international companies have particularly acutely felt the impact of the war in Ukraine on their functioning, which is caused by the destruction of logistics routes, a decrease in market demand as a result of consumer insolvency, etc. The success of management of international companies depends on the peculiarities of management, as well as on the type of international activity and the field of management of the enterprise under study. The coffee market is developing dynamically in the world, the intensification of its development in Ukraine took place about a decade ago. Due to the high demand in the market, Ukrainian enterprises are quite successful in selling imported coffee equipment, as well as using foreign supplies of coffee for the production of ready-made drinks. The study of an enterprise operating in the field of the coffee industry is currently an urgent issue that allows us to determine the prospects for the development of this area of domestic business.The article analyzes the current state of the world market of coffee machines and coffee, which shows that the United States imports the most coffee machines, with a share of 23 % in world imports. An important place in the import of this product occupied by Germany, France, Great Britain, Australia, and China, whose import shares range from 6.8 to 2.13 %.  The dynamics of import volumes of the TOP-10 importers of coffee machines to Ukraine in 2020-2022 analyzed. The geographical structure of imports of coffee machines to Ukraine in 2022 is studied. The conditions for importing coffee equipment from Italy to the countries of the largest importers identified. A comparison of tariffs for the import of coffee equipment from Romania to Ukraine and the largest import competitors carried out based on which promising directions for the development of the domestic coffee market and coffee equipment are proposed.
Keywords: world coffee market; export; import; export tariff